Social worker or social administrator? Findings from a qualitative case study of a child protection social work team. - Gibson, Matthew (Child & Family Social Work, 2017)
This paper reports on data from a qualitative case study of child protection social work in one local authority. Ethnographic methods were used and constructionist grounded theory employed to collect and analyse 329 pages of historical documents about the local authority child protection service, 246.5 hours of observations of social work practice and 19 interviews of social workers and their team managers. By interpreting the experiences of the social workers through the conceptual debates about the changes in the field of social administration, the social workers could be seen to want to perform a traditional form of social work but were required to perform a contemporary form of social administration. The aims and purposes of this form of practice could be considered to be distinct from those of social work as understood by the social workers, and as such, the social workers experienced the practice environment as constraining and often felt disillusioned. This paper conceptualizes these forms of practice, contributing to the debates about what practice is and how we are to analyse and categorize it for the purposes of influencing the institutions that create and maintain contemporary practice.